Reaching women who do not participate in the regular cervical cancer screening programme by offering self-sampling kits: A systematic review and meta-analysis of randomised trials - Verdoodt, F.; Jentschke, M.; Hillemanns, P.; Racey, C.S.; Snijders, P.J.F.; Arbyn, M. (European journal of cancer (1990), 2015)
Population coverage for cervical cancer screening is an important determinant explaining differences in the incidence of cervical cancer between countries. Offering devices for self-sampling has the potential to increase participation of hard-to-reach women. A systematic review and meta-analysis were performed to evaluate the participation after an invitation including a self-sampling device (self-sampling arm) versus an invitation to have a sample taken by a health professional (control arm), sent to under-screened women. Sixteen randomised studies were found eligible. In an intention-to-treat analysis, the pooled participation in the self-sampling arm was 23.6% (95% confidence interval (CI)=20.2–27.3%), when self-sampling kits were sent by mail to all women, versus 10.3% (95% CI=6.2–15.2%) in the control arm (participation difference: 12.6% [95% CI=9.3–15.9]). When women had to opt-in to receive the self-sampling device, as used in three studies, the pooled participation was not higher in the self-sampling compared to the control arm (participation difference: 0.2% [95% CI=−4.5–4.9%]). An increased participation was observed in the self-sampling arm compared to the control arm, if self-sampling kits were sent directly to women at their home address. However, the size of the effect varied substantially among studies. Since participation was similar in both arms when women had to opt-in, future studies are warranted to discern opt-in scenarios that are most acceptable to women.